A simple model to calculate the microstructure evolution in a NiTi SMA (Fracture and Structural Integrity, 2018)
Shape memory alloys (SMAs) are a wide class of materials characterized by the property to recover the initial shape. This property is due to ability of alloys to change the microstructure from a “parent” microstructure (usually called “Austenite”) to a “product” microstructure (usually called “Martensite”). Considering the tensile resistance, SMAs stress strain curves are characterized by a sort of plateau were the transformations from Austenite to Martensite (in loading condition) and from Martensite to Austenite (in unloading condition) take place. In this work a simple model to predict the microstructure modification has been proposed and verified with an equiatomic NiTi alloy characterized by a pseudo-elastic behavior.
Keywords: Shape memory alloy; Austenite; Martensite; Microstructure transitions